A European perspective on intercultural competence and prejudice: a cross-cultural analysis - Genkova, Petia; Schreiber, Henrik; Bogdanova, Pavlina; Lefringhausen, Katharina; Smokova, Liudmyla; Rašticová, Martina; Poor, Jozsef; Veresné, Klara Valentinyi; Suhajda, Csilla; Viszetenvelt, Andrea; Bjekic, Jovana (Frontiers in Social Psychology, 2025)
IntroductionThis study examines the relationship between intercultural competence and subtle and blatant prejudice toward refugees in Germany, the UK, Hungary, the Czech Republic, Ukraine, and Serbia.MethodUsing the Cultural Intelligence Scale and the Multicultural Personality Questionnaire, we analyze whether measures of intercultural competence are associated with lower levels of prejudice, with a particular focus on Eastern European contexts compared to established findings from Central Europe, North America, and East Asia.ResultsResults highlight cross-cultural differences in both the overall scales and their subdimensions in their associations with prejudice.DiscussionThese findings challenge the universal applicability of measures such as the Cultural Intelligence Scale and the Multicultural Personality Questionnaire, revealing that their effectiveness varies across cultural settings. The study underscores the necessity of culturally adapted interventions to address prejudice and foster social cohesion in regions experiencing increasing migration. By advancing a culturally nuanced perspective, this research contributes to refining intercultural competence methodologies and informing targeted integration policies that address region-specific challenges.